Uno spettacolo esemplare: Splendore e morte di Joaquín Murieta di Chéreau/Neruda al Piccolo Teatro (1970) - Cavaglieri, Livia (Mimesis Journal, 2017)
Taking into account documentary sources and new oral sources expressly created, the article reconstructs and analyses Splendore e morte di Joaquín Murieta by Pablo Neruda, directed by Patrice Chéreau in 1970 at Piccolo Teatro di Milano. It focuses on the general context of Italian “exile” experienced by Chéreau, on the role played in his poetics by the years in Milan, on dramaturgy and rehearsal, eventually on the relation at distance with his master Giorgio Strehler.